Vegetation dynamics of Mediterranean shrublands in former cultural landscape at Grazalema Mountains, South Spain - Gallego Fernández, Juan B.; Rosario García Mora, M.; García Novo, Francisco (Plant Ecology (formerly Vegetatio), 2004)
Plant community dynamics in Mediterranean basin ecosystems are mainly driven by an alternation of episodes of human intervention and land abandonment. As a result, a mosaic of plant communities has evolved following different stages of degradation and regeneration. Some authors has relate secondary succession to abandoned culture lands and regeneration to natural systems with abandonment of livestock or forestry exploitation. In this paper, the dynamics of shrublands in mid-mountain areas in the South of Spain after disturbance and land abandonment has been studied. The plant cover and 13 environmental variables of 137 selected sites on the Grazalema mountains was analysed to determine the vegetation pattern in relation to environmental factors and the succession types, either regenerative or secondary succession. The results show that today the Grazalema mountains have a heterogeneous vegetation pattern. Besides physical factors such as altitude or soil pH, human disturbance has modulated current vegetation patterns and dynamics. Two main types of vegetation dynamics can be distinguished in the study area. In areas affected by cutting, regeneration results in rich and dense shrub land, with resprouters as dominant species. In areas affected by recurrent wildﬁres or agriculture, secondary succession became dominant, resulting in less diverse shrubland, due to the dominance of seeders and decrease in resprouter species richness and cover.
Keywords: Human disturbance; Land abandonment; Mediterranean vegetation; Regen- erative succession; Regenerative strategies; Secondary succession